NILAI-NILAI MODERASI BERAGAMA DALAM BAHAN AJAR AKIDAH AKHLAK (TELAAH BUKU AJAR SISWA AKIDAH AKHLAK KELAS XI) - Rasmadi Rasmadi; Muslihudin; Akhmad Affandi (CV. ADIBA AISHA AMIRA, 2024)
An approach to religious moderation is important in developing balanced understanding, avoiding extremism and encouraging tolerance and interfaith dialogue. Within the scope of Islamic Religious Education, the values of religious moderation can be integrated into learning through textbooks and learning methods. This research aims to determine the characteristics of the Akidah Akhlak class XI textbook and determine the orientation of religious moderation values in the Akidah Akhlak class XI textbook. This research is a type of qualitative research through literature study. The class XI Akidah Akhlak textbook is the primary data source and related research journals are the secondary data source. Based on the results of the review of the Akidah Akhlak textbook, it meets the criteria for an ideal textbook. the concepts used in textbooks are clear, relevant to the curriculum, attract the interest of readers who use them, are able to motivate the users, can stimulate student activity, create illustrations that are able to attract their use, understanding must be preceded by appropriate communication, the content supports the subject others, respect individual differences, try to strengthen the values that apply in society, consider linguistic aspects according to the abilities of the students who use them, use clear concepts so as not to confuse students and have a clear point of view. The orientation to the values of religious moderation in the class starting from the introduction, core competencies, basic competencies, indicators, material in-depth, character in-depth, come on presentation and let's practice, especially on attitude assessment.